The effect of perceived parental rejection on depression in high school students: the chain mediating role of rumination and alexithymia - Li, Xiangyan; Lu, Quan; Wang, Yuxin; Gao, Yuan (Frontiers in Psychology, 2026)
In recent years, the incidence of depression in adolescents has continued to rise, which has become a hot issue of global concern. Through a cross-sectional survey, this study aims to explore the relationship between perceived parental rejection and depression in high school students, and to test the chain mediating effect of rumination and alexithymia in the relationship between them. A questionnaire survey was conducted among 2,310 high school students using the Short-from Egna Minnen av Barndoms Uppfostran for Chinese Scale, the Ruminative Responses Scale, the Toronto Alexithymia Scale and the Chinese version of Beck Depression Inventory-II (BDI-II). The results showed that parental rejection was positively correlated with depression in high school students. The mediating effects of rumination and alexithymia between parental rejection and depression were significant. Rumination and alexithymia played a chain mediating role between parental rejection and depression. Conclusion: Parental rejection not only directly predicts the depression levels of high school students, but also indirectly affects their depression through the independent mediating effects of rumination and alexithymia, as well as the chain mediating effect of rumination-alexithymia. This study constructs and validates this model for the first time, thereby deepening the understanding of the complex mechanism between parental rejection and depression in high school students and providing important insights for the prevention and intervention of depression.